Digital Wallets (Islamic Sciences Journal, 2023)
digital wallets are becoming increasingly important in our daily lives, to be used as a means of online marketing in addition to storage and payment through them, These wallets have many advantages such as speed and security in addition to being cheap, and they have several types, including what works without the internet and what does not work without it, Due to the rapid technological development, there are applications that work as digital wallets downloaded to smart devices, as they are not used as a communication tool only, but are used to shop through it and see goods, meaning that smart phones have begun to work like leather wallets that people carry to save money.
Keywords: Digital Wallet, Hot Wallet And Cold Wallet